From Digital Mental Health Interventions to Digital “Addiction”: Where the Two Fields Converge - Aboujaoude, Elias; Gega, Lina (Frontiers in Psychiatry, 2020)
Scientific literature from the last two decades indicates that, when it comes to mental health, technology is presented either as panacea or anathema. This is partly because researchers, too frequently, have planted themselves either in the field of digital mental health interventions (variably called “telepsychiatry”, “digital therapeutics”, “computerized therapy”, etc.), , or in that of the problems and risks arising from technology, with little cross-fertilization between the two. Yet, a closer look at the two fields reveals unifying themes that underpin both the advantages and dangers of technology in mental health. This article discusses five examples of such themes. First, the breakneck pace of technology evolution increases the potential of digital mental health interventions and creates ever more “addictive” activities, but leaves researchers perennially behind, so new technologies become outdated by the time they are studied. Second, the freedom of creating and using technologies in a regulatory vacuum has led to proliferation and choice, but also to a Wild-West online environment. Third, technology is an open window to access information, but also to compromise privacy, with serious implications for online psychology and digital mental health interventions. Fourth, weak bonds characterize online interactions, including those between therapists and patients, contributing to high attrition from digital interventions. Finally, economic analyses of technology-enabled care may show good value for money, but often fail to capture true cost, a fact that is mirrored in other online activities. The article ends with a call for collaborations between two interrelated fields that have been—till now—mutually insular.